Land management and crop cover effect on soil erosion in the humid lowlands of Beles River Sub-Basin, North-Western Ethiopia - Getnet Asfawesen Molla; Gizaw Desta (Journal of Degraded and Mining Lands Management, 2022)
Soil erosion is the most devastating environmental crisis in Ethiopia where the loss of soil from cultivated land is almost seven times the tolerable limit; specifically, Nitisol is very susceptible to erosion. To investigate the response of land management and cropping practices on sediment loss, a field experiment was conducted under natural environment on Nitisol of Pawi area. Nine treatments combining two tillage methods (zero and conventional), four crop covers (continuous maize, continuous soya bean, rotated maize, and maize soya bean intercrop), and continuous bare fallow as control were laid out in a randomized complete block design (RCBD) with three replications. The result showed that land management and crop cover significantly affect soil loss. Cultivation of crops without soil disturbance with full residue retention reduced soil loss by 6%, 36%, 36%, and 44% under soya bean, rotated maize, maize soya bean intercropping, and maize, respectively. Similarly, maize crop reduces soil loss by 34% under zero tillage management. Compared with conventionally managed maize crops, sediment concentration was also reduced by 14%, 17%, and 31%, maize with zero tillage, rotated maize with zero tillage, and maize soya bean intercropping with zero tillage, respectively. Except for zero-tilled maize soya bean intercropping and rotated maize, the seasonal soil loss was above the tolerable soil loss level of Ethiopia (2-10 t ha-1). This indicates there is a need for other management practices like physical and agronomic soil conservation methods to lower soil loss rates below the tolerable limit. Generally, zero tillage with greater crop cover is an appropriate approach to reduce soil loss by improving soil hydrological properties without negatively affecting grain yield. To understand and quantify the long-term impact of tillage and crop cover on soil health and productivity in Ethiopia long-term study is needed as this study was based on one-year data from four years of permanent plots.